2012
DOI: 10.1007/s11748-011-0810-4
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of oxidant-mediated biochemical injury and prompt functional recovery after prolonged single-dose crystalloid cardioplegic arrest in the infantile piglet heart by terminal warm-blood cardioplegia supplemented with phosphodiesterase III inhibitor

Abstract: We concluded that TWBCP with olprinone reduces myocardial reperfusion injury by reducing oxidant-mediated lipid peroxidation, and it accelerates prompt and persistent LV functional recovery with suppression of reperfusion arrhythmia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Direct comparisons between different cardioplegic solutions revealed that the modified Calafiore cardioplegia had a superior contractility after CBP surgery when compared to HTK [ 49 ]. For adult pig models, additives such as ebselene [ 50 ], olprinone [ 51 ], diazoxide [ 52 ], and sivelestat [ 53 ] have been investigated. A reduction in myocardial IRI with the antioxidants ebselene and olprinone has been proven [ 50 , 51 ].…”
Section: Investigations In Pediatric Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct comparisons between different cardioplegic solutions revealed that the modified Calafiore cardioplegia had a superior contractility after CBP surgery when compared to HTK [ 49 ]. For adult pig models, additives such as ebselene [ 50 ], olprinone [ 51 ], diazoxide [ 52 ], and sivelestat [ 53 ] have been investigated. A reduction in myocardial IRI with the antioxidants ebselene and olprinone has been proven [ 50 , 51 ].…”
Section: Investigations In Pediatric Modelsmentioning
confidence: 99%
“…For adult pig models, additives such as ebselene [ 50 ], olprinone [ 51 ], diazoxide [ 52 ], and sivelestat [ 53 ] have been investigated. A reduction in myocardial IRI with the antioxidants ebselene and olprinone has been proven [ 50 , 51 ]. Diazoxide protected the integrity of the mitochondrial structure when applied to a cardioplegic solution [ 52 ].…”
Section: Investigations In Pediatric Modelsmentioning
confidence: 99%
“…49,50 Studies in young pigs undergoing cardiopulmonary bypass have shown that inclusion of a phosphodiesterase III inhibitor (olprinone) in crystalloid cardioplegia improves recovery of left-ventricular function, reduces release of troponin-T and attenuates the development of arrhythmias. 49 Still, these drugs are positive inotropic agents that increase intracellular Ca 2+ levels 51 so they might be expected to actually exacerbate injury in cardioplegia. More studies of the underlying mechanisms are clearly needed.…”
Section: Other Pharmacological Strategiesmentioning
confidence: 99%
“…Other studies have used cardioplegia supplemented with a phosphodiesterase III inhibitor, based on reports that these agents can attenuate ischaemia and reperfusion injury possibly by reducing oxidative stress and cAMP‐, PKA‐, and p38 MAPK–dependent pathways . Studies in young pigs undergoing cardiopulmonary bypass have shown that inclusion of a phosphodiesterase III inhibitor (olprinone) in crystalloid cardioplegia improves recovery of left‐ventricular function, reduces release of troponin‐T and attenuates the development of arrhythmias . Still, these drugs are positive inotropic agents that increase intracellular Ca 2+ levels so they might be expected to actually exacerbate injury in cardioplegia.…”
Section: Pharmacologic Agents In Cardioplegia In Pre‐clinical Models mentioning
confidence: 99%